Designing new work-hardenable ductile Ti-based multilayered bulk metallic glass composites with ex-situ and in-situ hybrid strategy. (1st August 2020) - Lin, Shifeng; Zhu, Zhengwang; Ge, Shaofan; Zhang, Long; Liu, Dingming; Zhuang, Yanxin; Fu, Huameng; Li, Hong; Wang, Aimin; Zhang, Haifeng
Abstract: To overcome the trade-off between the devisable microstructure and the excellent tensile ductility of bulk metallic glass composites (BMGCs), a novel ex-situ and in-situ hybrid strategy is successfully proposed to design a series of the work-hardenable ductile Ti-based multilayered BMGCs (ML-BMGCs). The as-prepared ML-BMGCs, consisting of α-phases, β-phases and amorphous phases, exhibit a controllable multilayered structure of the Ti layers and the amorphous layers with alternative distribution. The size and volume fraction of the crystalline phases are tuned by Nb microalloying. It is found that the ML-BMGCs possess a suitable size and volume fraction of the crystalline phases when Nb microalloying content are 5% (at.) or 8% (at.), and they obtain an optimum combination of the specific strength of 243 MPa g kg 1 or 216 MPa g kg −1, and tensile plasticity of 4.33%±0.1% or 5.10%±0.1%. The deformation mechanism of the as-prepared ML-BMGCs during tension is also revealed. The ex-situ Ti layers and in-situ dendrites together effectively serve as absorbers to suppress the propagation of shear bands and multiply shear bands. And the deformation of ex-situ α-Ti phases by dislocation slip and the transformation from in-situ metastable β-Ti phase to orthorhombic α"-Ti during tension impart significant work-hardening capability to the ML-BMGCs. The present study provides a guidance of developing novel high-performance BMGCs with a controllable microstructure.